MODELS AND METHODS OF THE THEORY OF BUSINESS PROCESSES (REVIEW) - Georgiy N. Kalyanov (Открытое образование (Москва))
The basic directions of the modern theory of business processes. For each of these areas provides a brief overview of its main models and methods.